2004
DOI: 10.1007/s00198-003-1451-y
|View full text |Cite
|
Sign up to set email alerts
|

A method for assessment of the shape of the proximal femur and its relationship to osteoporotic hip fracture

Abstract: The shape of the proximal femur has been demonstrated to be important in the occurrence of fractures of the femoral neck. Unfortunately, multiple geometric measurements frequently used to describe this shape are highly correlated. A new method, active shape modeling (ASM) has been developed to quantify the morphology of the femur. This describes the shape in terms of orthogonal modes of variation that, consequently, are all independent. To test this method, digitized standard pelvic radiographs were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 9 publications
2
64
0
1
Order By: Relevance
“…In orthopedics, for example, researchers have applied shape models to the study of bone shapes and pathologies. In [48], Gregory, et al use a point-based modeling approach called Active Shape Modeling to study the correlation between proximal femur shapes and the rate of hip fracture in women. As with many other clinical shape studies, the goal of the hip fracture study is to develop an image-based assessment of the risk of the occurrence of the pathology.…”
Section: Other Applicationsmentioning
confidence: 99%
“…In orthopedics, for example, researchers have applied shape models to the study of bone shapes and pathologies. In [48], Gregory, et al use a point-based modeling approach called Active Shape Modeling to study the correlation between proximal femur shapes and the rate of hip fracture in women. As with many other clinical shape studies, the goal of the hip fracture study is to develop an image-based assessment of the risk of the occurrence of the pathology.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Several scientists measured independently geometric variables as HAL, u, a angle in clinical studies and they concluded that the geometric variation of proximal femur significantly contributes to the large variation in hip fracture risk [13][14][15][16][17][18][19][20][21][22][23][24][25] main topic inertia in minimum cross section of neck) and higher BR (buckling ratio) than controls without fractures [17], 4. u angle can be used to determine of the fracture risk independently of BMD [18], 5. patient with osteopenia measured in the total hip area may sustain a femoral neck fracture by fall, when she has adverse values of geometric variables of proximal femur (biomechanically unfavourable proximal femur configuration) [25], 6. there is a direct relationship between the predictor variable values BMI (body mass index), alpha angle, theta angle, and HAL and an categorical variable FNS value of <1, in that an increase of one relevant unit of measurement in these variables significantly increases the odds of fall-related fracture [12]. The contribution of our study lies in the finding of the 95% CI, within we can expect with 95% probability the mean values (m) of proximal femur geometric variables HAL, u angle, and a angle in the East Slovak female population.…”
Section: Discussionmentioning
confidence: 99%
“…Further, measures of proximal femur morphology from conventional radiographs predict hip fractures as well as BMD measurements [38] and improved correlation results when used in combination with BMD measures [31]. A two dimensional description of the proximal femur derived from an active shape model in combination with BMD measured at Ward's triangle prospectively classified 90 % of patients who had suffered a hip fracture [39]. Correlation models that combine BMD measurements with maximum principal strain predictions computed from two-dimensional finite element analysis (FEA) models and subject's height and neck shaft angle were able to correctly identify 82 % of subjects who previously reported a femoral fracture [40].…”
Section: Bone Strength Is a Function Of Bone Geometry Bmd And Bone mentioning
confidence: 99%